Inter- and Intrapersonal Skills of International Hospitality Professionals - Somlai, Réka (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The study focuses on extroversion personality trait and inter- and intrapersonal skills among Front Desk Agents in the hospitality industry in Hungary and Spain. The first aim of the study is to examine participants’ extroversion level. The second aim is to research what the soft skills are that Front Desk Agents find important to possess to be a successful employee. International comparison is important in both focus points. Findings are based on the results of an online survey. Participants are Hungarian and Spanish Front Desk Agents from various types of accommodations. The results suggest that both, Hungarian and Spanish participants consider themselves extroverted, on a fairly high level. Both Hungarians and Spanish participants find communication, problem solving, conflict resolution, stress management and empathy very important to be successful. They use similar skills at their everyday work like communication and customer orientation. Hungarians more often use practical skills like problem solving, Spaniards rather use skills that are related to creating a good atmosphere, such as friendliness and positive attitude. Both groups would teach communication, problem solving, empathy and customer orientation at tourism courses. Hungarians would add stress management, independency and conflict resolution; Spaniards also mention flexibility and patience. The results of this study can be used as a base for trainings for front desk agents at the hospitality industry and could be useful information for designing and organizing university courses.